Biodiversity Patterns and Ecological Preferences of the Photobionts Associated With the Lichen-Forming Genus Parmelia - Moya, Patricia; Molins, Arantzazu; Škaloud, Pavel; Divakar, Pradeep K.; Chiva, Salvador; Dumitru, Cristina; Molina, Maria Carmen; Crespo, Ana; Barreno, Eva (Frontiers in Microbiology, 2021)
The worldwide, ecologically relevant lichen-forming genus Parmelia currently includes 41 accepted species, of which the Parmelia sulcata group (PSULgp) and the Parmelia saxatilis group (PSAXgp) have received considerable attention over recent decades; however, phycobiont diversity is poorly known in Parmelia s. lat. Here, we studied the diversity of Trebouxia microalgae associated with 159 thalli collected from 30 locations, including nine Parmelia spp.: P. barrenoae, P. encryptata, P. ernstiae, P. mayi, P. omphalodes, P. saxatilis, P. serrana, P. submontana and P. sulcata. The mycobionts were studied by carrying out phylogenetic analyses of the ITS rDNA. The genetic diversity of Trebouxia spp. was screened by using the ITS rDNA and LSU rDNA markers. Species delimitation analyses were performed to estimate putative species boundaries in the Trebouxia and Parmelia datasets. All analyses clustered the mycobionts into two main groups: PSULgp and PSAXgp. Species delimitation identified 13 fungal and 15 algal species-level lineages. Diversity and abundance of Trebouxia spp. were assessed for each Parmelia species to identify patterns in specificity and selectivity at the species level. High specificity of each Parmelia group for a given Trebouxia clade was observed; PSULgp associated only with clade I and PSAXgp with clade S. However, the degree of specificity is different within each group, since the PSAXgp mycobionts were less specific and associated with 12 Trebouxia spp., meanwhile those of PSULgp interacted only with three Trebouxia spp. To identify the factors that shape the symbiotic partner distribution, variation-partitioning analyses were performed to detect the relative contributions of climate, geography, and symbiotic partner to phycobiont and mycobiont distribution patterns. Both analyses explained unexpectedly high portions of the variability (99% and 98%) and revealed strong correlation between the fungal and algal diversity. Network analysis discriminated seven ecological clusters. Even though the largest proportion of the variation among these clusters was explained by the climatic conditions, the seven clusters seemed to show indifference relative to climatic parameters. However, the cluster formed by P. saxatilis A/P. saxatilis B/Trebouxia sp. 2/Trebouxia sp. S02/Trebouxia sp. 3A was identified to prefer cold-temperateas well as humid summer environments.